Valve-Sparing Aortic Root Replacement Technique: Valsalva Graft versus Two Straight Tubular Grafts. (3rd February 2023) - Makkinejad, Alexander; Brown, Bailey; Ahmad, Rana-Armaghan; Hua, Joanna; Wu, Xiaoting; Fukuhara, Shinichi; Kim, Karen; Patel, Himanshu; Deeb, G. Michael; Yang, Bo
Abstract : Background . There are many variations in valve-sparing aortic root replacement techniques. Our aim is to determine the impact of the graft on mid-term outcomes: Valsalva graft vs. two straight tubular grafts. Methods . From 2004 to 2020, 332 patients underwent valve-sparing aortic root replacement with either a Valsalva graft (Valsalva group: n  = 270) or two straight tubular grafts (two-graft group: n  = 62). Data were obtained through chart review and the National Death Index. Primary outcomes were mid-term survival and freedom from reoperation. Results . The preoperative characteristics of the groups were similar, but the two-graft group had more type A dissections (32% vs. 19%) and emergent operations (26% vs. 15%) and was younger (45 vs. 50 years). Intraoperatively, the groups were similar, but the two-graft group had longer cross-clamp (245 vs. 215 minutes) and cardiopulmonary bypass times (284 vs. 255 minutes). Postoperative complications including reoperation for bleeding, stroke, pacemaker implantation, and renal failure were slightly more frequent in the Valsalva group, but the differences were not significant. Operative mortality was similar between the Valsalva and two-graft groups (0.7% vs. 0%). Five-year survival in the two-graft group was 100% compared to 96% in the Valsalva group (p = 0.56 ). Five-year freedom from reoperation in the two-graft group was 100% compared to 93% in the Valsalva group (p = 0.29 ). Conclusions . The Valsalva and two-graft techniques both have excellent short- and mid-term outcomes. The two-graft technique might have slightly better survival and freedom from reoperation, but a larger sample size and longer follow-up are needed to determine if these advantages are significant.